An Alternative Method for Preparing Methyl 2-Ferrocenyl-2-oxo-acetate - Pascal Pigeon; Hugo Hapel (Molbank, 2025)
Because of the continuous interest in ferrocene chemistry, there is a sustained demand for various ferrocenic building blocks, especially small molecules with useful chemical functional groups, sometimes containing multiple groups. Our interest in ferrocene ketoesters (ω-ferrocenyl-ω-ketoesters) was motivated by the synthesis of esters and subsequently alcohols of ferrociphenols. However, from a bibliographic survey, only one publication dated from 1964 reports the two-step synthesis (six-step synthesis from ferrocene) of methyl 2-ferrocenyl-2-oxoacetate, the simplest member of this family of compounds, with no further developments since. We hypothesized that a simpler method might exist, such as the Friedel–Crafts method. By focusing on our experiments to use aluminum trichloride as the catalyst, we managed to achieve the synthesis of FcCOCOOMe in a single step, albeit with a very low yield, regardless of reaction time, temperature, amount of aluminum chloride and reagents concentration. Nevertheless, considering the time saved, simplicity, and the use of less hazardous and less expensive reagents, this method offers certain advantages for synthesizing this building block.